Is cyclic guanosine 3',5'-monophosphate a cell cycle regulator? - Cook, W R (1980)
Transient increases in the intracellular level of cyclic guanosine 3',5'-monophosphate have been observed at a periodicity of one generation time in two spoT strains of Escherichia coli and in Bacillus licheniformis.